Inducement of agarwood resin using various chemical formulation of stem tissue (Aquilaria malaccensis) - Saripah Salbiah Syed Abdul Azziz (Tanjong Malim, 2019)
Inducement of agarwood resin using various chemical formulation of stem tissue (Aquilaria malaccensis) by Saripah Salbiah Syed Abdul Azziz